Lifelong Learning and Employability in the Danube Region Countries: Influences and Correlations - Constanţa-Nicoleta Bodea; Maria-Iuliana Dascălu; Gordana Velikic; Stelian Stancu (Amfiteatru Economic)
A continuous challenge for education and lifelong learning is to assist individuals in acquiring skills and knowledge for successful work life, especially after the financial crisis which influenced negatively the employment growth in all European Union countries. The paper focuses on finding correlations between employability and lifelong learning in the Danube Region countries of the European Union and more explicitly in the ex-communist ones of this region. As research instruments, two online questionnaires were built based on a thorough literature review and a set of structured interviews and filled in by 390 IT students and 55 IT professors. The surveys’ results revealed a clear positive correlation between the level of education and the opinion about the importance of obtaining a job as a result of the educational endeavors. A special attention in the survey was given to social networks, which were acknowledged as modern facilitators of lifelong learning activities. The conclusions of the current study are particularly important in the Romanian context, as the employment rate of recent graduates is in a decreasing trend, but also for all the Danube Region ex-communist countries, which have to boost their employment rates as well, to assure their economical growth. Identification of factors stimulating employment of young people according with their education contributes at the sustainable economic growth of these countries, at the growth of graduates insertion in the labor market and at the diminution of labor migration.